Doing Business in Argentina Challenges and Opportunities - Ovšák, Matúš (2013)
This thesis presents current business climate in Argentina. It aims to provide an overview of the investment environment and to extend previous studies by closer view on the energy industry. Its main findings are the following ones: Recent economic and political development rise concerns among policy makers and executives. Argentina applies strong interventionist policy and frequently interfere into the free market functioning. Among the most important issues are: foreign currency controls, manipulation of statistical results and noncompliance with its debt obligation. In various occasion expropriated private companies with aim of markets correction. The thesis also presents a case study of the Spanish company Repsol, whose investments in the Argentinean YPF were nationalized. According to my findings this act occurred under unconventional procedure and violated several laws and agreements. These policies resulted in the lower confidence among foreign investors. And despite that final figures for 2012 are still not available, there are various signs that the level of investment declines.